La2-xSrxCuO4 KUPRATI OʻTAOʻTKAZUVCHANLIK KRITIK HARORATINING BIR OʻQLI BOSIM BOʻYICHA HOSILAVIY QIYMATLARI - Sh.Kabulov, I.; Jalekeshov, A.S.; Ya.Yavidov, B. (SCIENCE and SOCIETY, 2022)
The article considers the superconductivity of cuprate La2-xSrxCuO4 within the framework of the Holstein-Hubbard model and the approximation of bipolaronic superconductivity. The temperature of the Bose-Einstein condensation of an ideal gas of two-site bipolarons is taken as the critical temperature of cuprate superconductivity. The temperature of the Bose-Einstein condensation of an ideal gas of two-site bipolarons is expressed in terms of the strains of the cuprate crystal lattice, and the values of its derivatives with respect to uniaxial pressures are calculated at various levels of doping. The dependence of the values of the temperature derivative of the Bose-Einstein condensation of an ideal gas of two-site bipolarons with respect to uniaxial pressures on the value of the elastic constants of the cuprate crystal lattice is emphasized.
Keywords: cuprates; superconductivity; critical temperature; uniaxial strain; uniaxial pressure; bipolaron; Bose-Einstein condensation